5′ValCAC tRNA fragment generated as part of a protective angiogenin response provides prognostic value in amyotrophic lateral sclerosis. Issue 2 (28th August 2020) - Hogg, Marion C; Rayner, Megan; Susdalzew, Sergej; Monsefi, Naser; Crivello, Martin; Woods, Ina; Resler, Alexa; Blackbourn, Lisle; Fabbrizio, Paola; Trolese, Maria Chiara; Nardo, Giovanni; Bendotti, Caterina; et al.
Abstract: Loss-of-function mutations in the ribonuclease angiogenin are associated with amyotrophic lateral sclerosis. Angiogenin has been shown to cleave transfer RNAs during stress to produce 'transfer-derived stress-induced RNAs'. Stress-induced tRNA cleavage is preserved from single-celled organisms to humans indicating it represents part of a highly conserved stress response. However, to date, the role of tRNA cleavage in amyotrophic lateral sclerosis remains to be fully elucidated. To this end, we performed small RNA sequencing on a human astrocytoma cell line to identify the complete repertoire of tRNA fragments generated by angiogenin. We found that only a specific subset of tRNAs is cleaved by angiogenin and identified 5′ValCAC transfer-derived stress-induced RNA to be secreted from neural cells. 5′ValCAC was quantified in spinal cord and serum from SOD1 G93A amyotrophic lateral sclerosis mouse models where we found it to be significantly elevated at symptom onset correlating with increased angiogenin expression, imbalanced protein translation initiation factors and slower disease progression. In amyotrophic lateral sclerosis patient serum samples, we found 5′ValCAC to be significantly higher in patients with slow disease progression, and interestingly, we find 5′ValCAC to hold prognostic value for amyotrophic lateral sclerosis patients. Here, we report that angiogenin cleaves a specific subset of tRNAs and provide evidence for 5′ValCAC as a prognostic biomarker in amyotrophic lateral sclerosis. We propose that increased serum 5′ValCAC levels indicate an enhanced angiogenin-mediated stress response within motor neurons that correlates with increased survival. These data suggest that the previously reported beneficial effects of angiogenin in SOD1 G93A mice may result from elevated levels of 5′ValCAC transfer RNA fragment. Abstract : Angiogenin is a stress-induced ribonuclease linked to amyotrophic lateral sclerosis via pathogenic loss-of-function mutations. Here we investigate substrates of Angiogenin and identify 5′Valine CAC tRNA fragment as a prognostic biomarker in mouse models and in serum samples from patient with Amyotrophic Lateral Sclerosis, where higher levels are associated with longer survival. Graphical Abstract: